Occurrence of overweight in schoolchildren and analysis of agreement between anthropometric methods - Robson Damasceno de Lima; Rodrigo Martins Pereira; Vitor Rosetto Muñoz; Raphael dos Santos Canciglieri; Paulo Henrique Canciglieri (Revista Brasileira de Cineantropometria e Desempenho Humano)
The child population is strongly affected by obesity. Accessible and reliable strategies for the obesity diagnosis are of utmost importance. The aim of this study was to identify childhood obesity according the WHO (World Health Organization): malnourished, healthy weight, overweight and obese. It was collected measures of height, Body Mass Index (BMI), Waist Circumference (WC) and Triceps Skinfold Thickness (TSF) of 449 children from Municipal School of Araras/SP, from 7 to 10 years old. It was performed a Spearman correlation test between BMI, WC and TSF variables. Also, was realized cross tabulation between the found results by the different methods, constructing a contingency table 2x2, with absolute frequency of boys and girls classified as “without overweight” and “with overweight”. The concordance between methods was analyzed by kappa index. In the results, 28.3% of children presented overweight according to BMI, with higher prevalence in boys. Generally, the found results through TSF showed strong correlation with both BMI and WC (rs=0.7994 e rs=0.7519, respectively). The same was observed when data was analyzed separately by sex. When crossed the TSF data with BMI and WC, the kappa index demonstrated a satisfactory concordance (0.4419 e 0.5161, respectively). The TSF can be suggested a method to body composition assessment and cardiometabolic risk in children.